PD‐1/PD‐L1 Blockade Therapy in Advanced Non‐Small‐Cell Lung Cancer: Current Status and Future Directions - Xia, Liliang; Liu, Yuanyong; Wang, Ying (The oncologist (Dayton, Ohio), 2019)
The use of immune checkpoint inhibitors (ICIs) has become one of the most promising approaches in the field of cancer therapy. Unlike the current therapies that target tumor cells, such as chemotherapy, radiotherapy, or targeted therapy, ICIs directly restore the exhausted host antitumor immune responses mediated by the tumors. Among multiple immune modulators identified, the programmed cell death protein 1 (PD‐1)/programmed cell death protein ligand 1 (PD‐L1) axis leading to the exhaustion of T‐cell immunity in chronic infections and tumors has been widely investigated. Therefore, blocking antibodies targeting PD‐1 or PD‐L1 have been developed and approved for the treatment of various advanced cancers, including non‐small‐cell lung cancer (NSCLC), making them the most successful ICIs. Compared with chemotherapy or radiotherapy, PD‐1/PD‐L1 blockade therapy significantly improves the durable response rate and prolongs long‐term survival with limited adverse effects in both monotherapy and combination therapy for advanced NSCLC. However, extensive challenges exist for further clinical applications, such as a small fraction of benefit population, primary and acquired resistance, the lack of predictive and prognostic biomarkers, and treatment‐related adverse effects. In this article, we summarize the latest clinical applications of PD‐1/PD‐L1 blockade therapy in advanced NSCLC worldwide, as well as in China, and discuss the bottlenecks related to the use of this therapy in clinical practice. An exploration of the underlying mechanism of PD‐1/PD‐L1 blockade therapy and biomarker identification will maximize the application of ICIs in advanced NSCLC and facilitate bedside‐to‐bench studies in cancer immunotherapy as well. Implications for Practice Immune checkpoint inhibitors (ICIs) targeting programmed cell death protein 1 (PD‐1) and programmed cell death protein ligand 1 (PD‐L1) display apparent benefits for the treatment of advanced non‐small‐cell lung cancer (NSCLC). However, the clinical applications of these therapies are challenged by the limited benefit population with additional high economic burden and adverse events. This review discusses the bottlenecks of ICI therapy in clinical practice and provides appropriate guidance in the development of predictive biomarkers, the establishment of the criteria for combining PD‐1/PD‐L1 blockade therapy with the existing therapies, and the management of adverse events observed both in monotherapy and combination therapy, which will help maximize the applications of ICIs in advanced NSCLC. 摘要 免疫检查点抑制剂 (ICI) 的使用已成为癌症治疗领域最具前景的方法之一。与靶向肿瘤细胞的现有疗法(如化疗、放疗或靶向治疗)不同，ICI 可直接恢复由肿瘤介导的耗竭的宿主抗肿瘤免疫应答。在已确定的多种免疫调节剂中，已经广泛研究了导致慢性感染和肿瘤中 T 细胞免疫耗竭的程序性细胞死亡蛋白 1 (PD‐1)/程序性细胞死亡蛋白配体 1 (PD‐L1) 轴。因此，已经开发了靶向 PD‐1 或 PD‐L1 的阻断抗体，并批准用于治疗各种晚期癌症，包括非小细胞肺癌 (NSCLC)，这使其成为最成功的 ICI。在晚期 NSCLC，与化疗或放疗相比，PD‐1/PD‐L1 阻断治疗无论单药和联合治疗均明显提高了持久缓解率并延长了长期生存，而且不良反应很少。然而，对于进一步的临床应用却存在大量挑战，例如，仅有小部分群体受益，存在原发性和获得性耐药，缺乏预测和预后生物标志物，以及存在治疗相关不良反应。在本文中，我们总结了中国及全球范围内 PD‐1/PD‐L1 阻断治疗在晚期 NSCLC 中的最新临床应用，并讨论了在临床实践中使用该疗法的瓶颈。对 PD‐1/PD‐L1 阻断治疗和生物标志物鉴定的潜在机制的探索将最大化 ICI 在晚期 NSCLC 中的应用，同时，也将促进癌症免疫治疗“从临床到实验室”的研究。 实践意义:在晚期非小细胞肺癌 (NSCLC) 的治疗中，靶向程序性细胞死亡蛋白 1 (PD‐1) 和程序性细胞死亡蛋白配体 1 (PD‐L1) 的免疫检查点抑制剂 (ICI) 呈现出明显益处。然而，这些治疗的临床应用却面临着受益群体有限、额外的高昂经济负担和不良事件等挑战。本篇综述讨论了 ICI 疗法在临床实践中的瓶颈，并为预测生物标志物的形成、将 PD‐1/PD‐L1 阻断治疗与现有治疗相结合的标准确立、以及在单药和联合治疗中观察到的不良事件的管理提供了适当的指导，从而有助于最大化 ICI 在晚期 NSCLC 中的应用。 This article summarizes the latest clinical applications of PD‐1/PD‐L1 blockade therapy in advanced non‐small cell lung cancer (NSCLC) worldwide and in China, reporting the bottlenecks related to the use of this therapy in clinic. An exploration of the underlying mechanism of PD‐1/PD‐L1 blockade therapy and biomarker identification will maximize the application of immune checkpoint inhibitors in advanced NSCLC and facilitate bedside‐to‐bench studies in cancer immunotherapy.